Węgajty Theatre: creating a place - Budzowska, Małgorzata; Michalik-Tomala, Justyna; Prykowska-Michalak, Karolina; Królikowska, Joanna (Relacyjność w kulturze i sztuce: Księga jubileuszowa Profesor Małgorzaty Leyko, 2025)
The article concerns the Węgajty Theatre, focusing on the construction of a place for theatrical activities and the everyday life of Erdmute and Wacław Sobaszek, co-founders and leaders of the Węgajty Theatre. In the context of the Warmia region and the micro-histories of Erdmute and Wacław's families the history of the place is presented. Material aspects of the place concerning the space of the Węgajty homestead are analysed: buildings and the natural world, culture and na-ture coexistence, and the creation of the place through theatrical practices, such as forest runs. The article indicates the concomitance of a theatre and a house in one homestead, public and private spaces intermingling, and artistic activities ac-companying daily life. The Węgajty Theatre is recognised as a heterotopia, Michel Foucault's concept of "other" space, open and closed simultaneously, where time changes and reality is condensed. Author demonstrates that the Węgajty Theatre is a place which creates relations and is built by them at the same time.